Effect of ammonia on lysinoalanine formation in proteins by alkali treatment - SHIMIZU, Yoko; MUKAI, Kaori; MATOBA, Teruyoshi; HASEGAWA, Kiyozo; MURATA, Rie (Nippon Nōgeikagaku Kaishi, 1986)
Alkali treatment of protein in the presence of ammonia formed β-aminoalanine (β-AA). Quantitative determination of β-AA was performed by mass chromatography. When α-lactalbumin or phosvitin was heated in the presence of ammonia under alkali condition, lysinoalanine (LAL) formation was suppressed. Its suppression was due to formation of β-AA. This significant suppression of both proteins by ammonia was observed at 55°C and 95°C, but not at 30°C.